Tocilizumab for thyroid eye disease - Hamed Azzam, Shirin (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The aim of this review is to investigate the efficacy and safety of tocilizumab for the treatment of people with TED.